2021
DOI: 10.1097/md.0000000000027904
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemolysis and methemoglobinemia secondary to fava beans ingestion in a patient with G6PD deficiency

Abstract: Rationale: Favism is a well-known cause of acute hemolytic anemia. Rarely, methemoglobinemia can also happen because of fava bean ingestion in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency. Few cases with this co-occurrence have been reported in the literature.Patient concerns: We report a case of a 47-year-old patient who presented with jaundice that started 2 days after eating fava beans.Diagnoses: Laboratory investigations revealed anemia with evidence of hemolysis (high reticulocytes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…He was diagnosed with G6PD deficiency (23 mU/10 9 RBC, normal value: 224–517 mU/10 9 RBC), and was discharged as he became asymptomatic on the fifth day. Al-Dubai H et al [ 43 ] reported the case of a 47-year-old man with a 3 day history of yellowish eyes and dark urine, arising two days after a medium-sized plate of broad beans. On physical examination, there was jaundice, methemoglobin level of 3.6%, and a decreased oxygen saturation, which was resistant to supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…He was diagnosed with G6PD deficiency (23 mU/10 9 RBC, normal value: 224–517 mU/10 9 RBC), and was discharged as he became asymptomatic on the fifth day. Al-Dubai H et al [ 43 ] reported the case of a 47-year-old man with a 3 day history of yellowish eyes and dark urine, arising two days after a medium-sized plate of broad beans. On physical examination, there was jaundice, methemoglobin level of 3.6%, and a decreased oxygen saturation, which was resistant to supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…The co-occurrence of hemolysis and methemoglobinemia in G6PD deficiency is uncommon. Few cases were stated in the literature reported co-occurrence of hemolysis and methemoglobinemia in G6PD deficiency secondary to a known inciting event due to hydroxychloroquine, rasburicase, fava beans ingestion, and secondary to acute infections [11][12][13]17,18]. A case reported described such an event following hepatitis E virus infection in a patient with G6PD deficiency [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, G6PD deficiency leads to hemolysis following oxidative stress. (3) Inadequate NADPH levels lead to heme iron oxidation to ferric rather than ferrous state. Resultant methaemoglobin causes increased oxygen affinity with impaired oxygen delivery and tissue hypoxia.…”
Section: Discussionmentioning
confidence: 99%